Effect of Madden Julian oscillation on convectively coupled equatorial waves - Dobriyal, Ritvik (2019)
Effect of Madden Julian oscillation (MJO) on convectively coupled equatorial waves (CCEW) is studied using TRMM-3B42 precipitation dataset. The investigation is carried out for the two seasons of DJFM (December January February March) and JJAS (June July August September). Key finding for both seasons is that when MJO enhances precipitation, wave activity becomes stronger, while when MJO suppresses convection wave activity is weakened. Greater effect of MJO on CCEW is noticed over the zonal extent in which the convective component of MJO is strong, ranging from the Indian Ocean to western Pacific Ocean (nearly 60°E to 180°). MJO is also found to affect CCEW over Africa and near South America if wave activity peaks in these regions, however the effect is nearly half as strong or weaker. In order to understand the impact of MJO on CCEW, a simplified theoretical model of convectively coupled waves is employed. Since MJO has a larger spatial structure and greater time period as compared to CCEW, therefore the theoretical model is modified by using MJO as a background. Fluctuations in barotropic wind, baroclinic shear and diabatic heating due to MJO are considered in the background. Linear analysis of the theoretical model reveals that out of the three factors considered, fluctuations in diabatic heating due to MJO is the dominant factor affecting CCEW. Effect of diabatic heating on the instability mechanism of the model, affecting the evolution of convectively coupled waves is explored.